2013
DOI: 10.4236/ampc.2013.31009
|View full text |Cite
|
Sign up to set email alerts
|

Thickness Dependence of Dielectric Characteristics of SrTiO<sub>3</sub> Thin Films on MgAl<sub>2</sub>O<sub>4</sub> Substrates

Abstract: SrTiO 3 (STO) thin films of different thicknesses were deposited on MgAl 2 O 4 (MAO) substrates to investigate the in-plane strain effect on the soft-mode frequency of the STO films. X-ray reciprocal space mapping (X-RSM) results indicate that there was no relaxation of the in-plane lattice strain of the STO films on MAO. Shifts in the soft-mode frequencies with a decrease in the film thickness were observed using terahertz time-domain spectroscopy (THz-TDS). However, despite the larger lattice mismatch betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…In the context of organic thin film transistors, it has been observed that increased surface roughness in the gate dielectric leads to a higher density of grain boundaries, resulting in an increased presence of trap states in the semiconductor layer 25 , 26 . In the field of heteroepitaxy, where a crystal or thin film is grown on a substrate with a different lattice constant, it is well-documented that the quality of deposited crystals can change significantly depending on the condition of the underlayer crystal interface, potentially leading to the formation of dislocations or defects 27 , 28 . Although perovskite films in PSCs differ from these materials, as they are primarily fabricated using spin-coating techniques and are generally polycrystalline, it is conceivable that modifications at the interface between the TiO 2 and perovskite layers could affect not only the junction state but also the crystallinity of the grown perovskite layer.…”
Section: Introductionmentioning
confidence: 99%
“…In the context of organic thin film transistors, it has been observed that increased surface roughness in the gate dielectric leads to a higher density of grain boundaries, resulting in an increased presence of trap states in the semiconductor layer 25 , 26 . In the field of heteroepitaxy, where a crystal or thin film is grown on a substrate with a different lattice constant, it is well-documented that the quality of deposited crystals can change significantly depending on the condition of the underlayer crystal interface, potentially leading to the formation of dislocations or defects 27 , 28 . Although perovskite films in PSCs differ from these materials, as they are primarily fabricated using spin-coating techniques and are generally polycrystalline, it is conceivable that modifications at the interface between the TiO 2 and perovskite layers could affect not only the junction state but also the crystallinity of the grown perovskite layer.…”
Section: Introductionmentioning
confidence: 99%
“…The soft-mode frequency of the STO bulk material was reported to be in the range of 2.7-3.0 THz and determined by the thickness, interface stress, temperature, electric field, and other factors. [20][21][22][23][24][25][26][27][28][30][31][32][33] When an 800 nm CW laser irradiates the sample, temperature variation is inevitably introduced. To further characterize the temperature-dependent optical parameters of the STO/Si sample, the THz time-domain waveforms were measured at different temperatures and illustrated in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The dielectric tunability of the STO thin films under an optical field, however, has rarely been reported as it is difficult to identify the dielectric properties of ferroelectric thin films and they exhibit process-dependent properties. [27][28][29][30] Moreover, considerably fewer studies have focused on the THz regime. In this work, we investigated the active control of optical parameters of the STO thin film grown on silicon substrate (STO/Si) under the irradiation of an 800 nm laser.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, there has been few discussions on deposited perovskite crystal itself affected by the surface treatment in the studies. However, it has been well discussed in the eld of heteroepitaxy method in which a crystal or thin lm is grown on a substrate with a different lattice constant, that the quality of the deposited crystals changes signi cantly depending on a condition of the interface of the underlayer crystals as it can cause a formation of dislocations or defects 21,22 . Although perovskite thin lms in PSC devices are different from the heteroepitaxy method that perovskite lms are mainly fabricated by a spin coating method and are basically a multi crystal while heteroepitaxy method mainly performed with a single crystal, not only the junction state but also the crystallinity of the grown perovskite layer may possibly change by an interface modi cation for TiO 2 and perovskite layers.…”
Section: Main Textmentioning
confidence: 99%